![lg(tg(30)*tg(32)*...*tg(58)*tg(60)) lg(tg(30)*tg(32)*...*tg(58)*tg(60))](https://tex.z-dn.net/?f=lg%28tg%2830%29%2Atg%2832%29%2A...%2Atg%2858%29%2Atg%2860%29%29)
![tg(\alpha)*tg(\beta) = \frac{cos(\alpha - \beta) - cos(\alpha + \beta)}{cos(\alpha - \beta) + cos(\alpha + \beta)} tg(\alpha)*tg(\beta) = \frac{cos(\alpha - \beta) - cos(\alpha + \beta)}{cos(\alpha - \beta) + cos(\alpha + \beta)}](https://tex.z-dn.net/?f=tg%28%5Calpha%29%2Atg%28%5Cbeta%29%20%3D%20%5Cfrac%7Bcos%28%5Calpha%20-%20%5Cbeta%29%20-%20cos%28%5Calpha%20%2B%20%5Cbeta%29%7D%7Bcos%28%5Calpha%20-%20%5Cbeta%29%20%2B%20cos%28%5Calpha%20%2B%20%5Cbeta%29%7D)
![image](https://tex.z-dn.net/?f=tg%2860%29%20%2A%20tg%2830%29%20%3D%20%5Cfrac%7Bcos%2830%29%20-%20cos%2890%29%7D%7Bcos%2830%29%20%2B%20cos%2890%29%7D%20%3D%20%5Cfrac%7Bcos%2830%29%7D%7Bcos%2830%29%7D%20%3D%201%20%5C%5C%3C%2Fp%3E%3Cp%3Etg%2858%29%20%2A%20tg%2832%29%20%3D%20%5Cfrac%7Bcos%2826%29%20-%20cos%2890%29%7D%7Bcos%2826%29%20%2B%20cos%2890%29%7D%20%3D%20%5Cfrac%7Bcos%2826%29%7D%7Bcos%2826%29%7D%20%3D%201%20%5C%5C%3C%2Fp%3E%3Cp%3E...%20%5C%5C%3C%2Fp%3E%3Cp%3Etg%2846%29%2Atg%2844%29%20%3D%20%5Cfrac%7Bcos%282%29%20-%20cos%2890%29%7D%7Bcos%282%29%20%2B%20cos%2890%29%7D%20%3D%20%5Cfrac%7Bcos%282%29%7D%7Bcos%282%29%7D%20%3D%201)
tg(58) * tg(32) = \frac{cos(26) - cos(90)}{cos(26) + cos(90)} = \frac{cos(26)}{cos(26)} = 1 \\
... \\
tg(46)*tg(44) = \frac{cos(2) - cos(90)}{cos(2) + cos(90)} = \frac{cos(2)}{cos(2)} = 1" alt="tg(60) * tg(30) = \frac{cos(30) - cos(90)}{cos(30) + cos(90)} = \frac{cos(30)}{cos(30)} = 1 \\
tg(58) * tg(32) = \frac{cos(26) - cos(90)}{cos(26) + cos(90)} = \frac{cos(26)}{cos(26)} = 1 \\
... \\
tg(46)*tg(44) = \frac{cos(2) - cos(90)}{cos(2) + cos(90)} = \frac{cos(2)}{cos(2)} = 1" align="absmiddle" class="latex-formula">
![lg(tg(30)*tg(32)*...*tg(58)*tg(60)) = lg(1) = 0 lg(tg(30)*tg(32)*...*tg(58)*tg(60)) = lg(1) = 0](https://tex.z-dn.net/?f=lg%28tg%2830%29%2Atg%2832%29%2A...%2Atg%2858%29%2Atg%2860%29%29%20%3D%20lg%281%29%20%3D%200)